The Comparison of Indonesian and Singaporean Defence in Regional Security from Critical Analysis Perspective - Asrudin, Muhammad (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Singapore and Indonesia's defence strategies are shaped by significant differences in terms of area and length of coastline. While Singapore's compact size makes it vulnerable to invasion, it also allows for the concentration of military resources within a smaller perimeter. A study was conducted to report a literature analysis that focused on analysis of Global Firepower that tracks military power information from 145 countries in the world. We identified and analyse the comparison of Singapore and Indonesia Military Strengths in 2024. The main purpose of this research is to identify and present relevant information without conducting experiments or direct observation.